Utilization of Fermented Pistia stratiotes L. Flour in Diet for Growth Asian Redtail Catfish (Hemibagrus nemurus) - Geri Gunawan; Adelina Adelina; Indra Suharman (Universitas Riau, 2021)
Asian redtail catfish (Hemibagrus nemurus) are fish that have high economic value. The Aimed of this study was to know of the effect the use of fermented Pistia stratiotes flour and to know the percentage of best P. stratiotes flour fermentation on the growth of Asian redtail catfish fingerling. The method in this study is a completely randomized design (CRD) with five treatments and three replications, the treatments are P0 (100% soybean flour, 0% fermented P. stratiotes flour), P1 (TK 95%, TKAT 5%), P2 (P2 TK 90%, TKAT 10%), P3 (TK 85%, TKAT 15%), and P4 (TK 80%, TKAT 20%). The fish used were 5.00 ± 1.00 cm long and weighed 1.50 ± 0.50 g, with a stocking density of 20 fish/m3. Fish are kept for 56% with a frequency of feeding three times a day. The results showed that the substitution of fermented P. stratiotes flour was able to effect the growth of Asian redtail catfish. The dosage of fermented P. stratiotes flour as much as 15% gives the best results on the growth of Asian redtail catfish, namely the specific growth rate (SGR), feed efficiency, and survival rate of 3.93%, 46.47% and 96.7%.